Pengaruh Pemberian Ekstrak Etanol Daun Ketepeng Cina (Cassia Alata L.) Terhadap Waktu Pendarahan, Pembekuan Darah dan Jumlah Trombosit Mencit Putih Jantan - Sri Oktavia; Selvina Pebryantika; Surya Dharma (STIFARM Padang, 2015)
Research on the effect of ethanol extract of ketepeng cina (Cassia alata L.) on bleeding time, blood clotting and platelet count male white mice. Extracts ketepeng cina (Cassia alata L.) given to male white mice that had been induced with phenytoin natrium. Animal experiment is divided into 4 groups, each group consisted of 5 mice. Group 1 (control) was given phenytoin natrium at a dose of 100 mg/kg BW, group II given ketepeng cina extract dose of 100 mg/kg BW, group III given ketepeng cina extract dose 300 mg/kg BW, group IV given ketepeng cina extract at a dose of 900 mg/kg BW. Before given phenytoin natrium, groups 1 to 4 were measured prior bleeding time, blood clotting and platelet counts on day 0 as control, then given phenytoin natrium from day 0 to day 14 and continued with the administration of the test substance to-8 to day 21. Effect observased day-to-7, 14,and 21. The results showed the extract of ketepeng cina (Cassia alata L.) at a dose of 100, 300, and 900 mg/kg BW orally can affect shorten bleeding time, blood clotting and increase the number of platelet male white mice day-to-21 and the most effective dose is the dose of 900 mg/kg BW.